Zasada słuszności jako przesłanka odpowiedzialności władzy publicznej: brak - Konieczna, Kinga (Studia Prawnoustrojowe, 2019)
This article presents the issue of liability for legal damages caused by public authorities. It contains analyses of the premises and current problems concerning this type of civil liability. Various points of view are presented for theoretical aspects of the topic and their inﬂuence on the application of the discussed regulations in practice. The author proposes solutions for the future that may contribute to strengthening the legal protection of the victims.